Answer:
C
Explanation:
Since we are dealing with recursive equations, we can use a simple format.
![a_(1)=x \\ \\ a_(n)=a_(n-1)+y](https://img.qammunity.org/2020/formulas/mathematics/high-school/26brlxs8cu5yc52vtkrrkuxecfsdjfiozt.png)
x is the starting value and y is the change.
We can see that the change is -5.6 since 5.6 is being subtracted from each term each time.
So the equation would be
![a_n=a_(n-1)-5.6](https://img.qammunity.org/2020/formulas/mathematics/high-school/px3qhyqhpnzy7iye8gybflbotyzbrra23g.png)
We can check this by plugging in the numbers.
Let's see if -8.3 works, which is the 2nd term in the equation.
![a_2=a_(2-1)-5.6 \\ \\ -8.3=a_(1)-5.6 \\ \\ -8.3=-2.7-5.6 \\ \\ -8.3=-8.3](https://img.qammunity.org/2020/formulas/mathematics/high-school/j6hh79cp5ju3w6ularby3ymbo7u5rspvzs.png)
Therefore, the recursive rule is the third one.